The application of electrical resistivity tomography (ERT), induced polarization (IP) and electromagnetic conductivity (EMC) methods for the evaluation of technical condition of flood embankment corpus - Cygal, Adam; Stefaniuk, Michał; Kret, Anna; Kurowska, Monika (Geology, Geophysics and Environment, 2017)
A series of catastrophic floods that have occurred over the last twenty years in Poland brought an urgent need for taking preventive steps to monitor river embankment conditions. The main problem seems to be the development of efficient (i.e. fast and economical) measurements for controlling the condition of river embankments, because the execution of the full range of geotechnical measurements is both lengthy and costly. In this situation, a cheap and quick geophysical survey has been proposed to undertake this purpose. In this article the results of geophysical surveys are described which were performed using geoelectric and electromagnetic methods along a section of the Vistula embankment, located near the Maniów area in the Małopolska province. According to the archival data, this region is situated in a high-risk flooding zone. Three geophysical methods were used to recognize conditions of the levee: (i) Electrical Resistivity Tomography (ERT), (ii) Induced Polarization (IP) and (iii) Electromagnetic Conductivity (EMC). Geoelectrical measurement results were presented in the form of resistivity and polarization cross-sections. Results of conductivity measurement were presented in the form of plots. These parameters effectively supplement geotechnical testing, providing spatial information about the changes within the embankment and its substrate. It allows the prediction of potentially vulnerable areas to water percolation during flooding.